Penggambaran Legenda Sangkuriang Melalui Karya Tari “Sumbi Raksa” Menggunakan Metode Moving From Within Alma M.Hawkins - Bunga Arulia Gibran; Ida Bagus Ketut Sudiasa; Deden Haerudin (Program Studi Pendidikan Tari FBS UNJ, 2023)
The Sumbi Raksa dance work is taken from a scene from the Legend of Sangkuriang which tells of Dayang Sumbi's inner war, namely feelings of love, longing mixed with anger, annoyance, confusion, disappointment over the fact that Sangkuriang is his child and the feeling of happiness to be reunited with his child.Sumbi is taken from the name of a figure from Dayang Sumbi and Raksa means to guard and is taken from the word rasa which means feeling. In this dance work, it tells about Dayang Sumbi who tries to protect her heart from her feelings of love and affection for Sangkuriang.The purpose of creating this dance is to convey moral and ethical values to society, how important it is for us to control our emotions and feelings in responding to a reality, even though sometimes it is not what we expect and inbreeding is not allowed because if a gene unites bad things will happen to their life.The dance work method uses Moving From Within from Alma M Hawkins. Book entitled